2007
DOI: 10.1038/sj.bjc.6603555
|View full text |Cite
|
Sign up to set email alerts
|

Frequent reduced expression of alpha-1B-adrenergic receptor caused by aberrant promoter methylation in gastric cancers

Abstract: Recent studies have suggested that epigenetic inactivation of tumour-related genes by promoter methylation participates in the development of gastric cancer. We newly identified the frequently aberrant promoter methylation of alpha-1B-adrenergic receptor (ADRA1B) in colorectal cancer by methylation-sensitive representational difference analysis (MS-RDA) and examined the methylation status of the ADRA1B promoter in 34 paired samples of colorectal cancer and surrounding epithelial tissue, and 34 paired samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…ADRA1B is a member of the GPCRs, and it has been reported that this gene is closely related to the prognosis of thyroid papillary carcinoma [ 47 ]. Studies have shown that the methylation of ADRA1B plays a key role in the occurrence and development of GC [ 48 , 49 ]. Our study showed that the expression of ADRA1B in GC tissues was lower than that in adjacent tissues, which may be related to methylation.…”
Section: Discussionmentioning
confidence: 99%
“…ADRA1B is a member of the GPCRs, and it has been reported that this gene is closely related to the prognosis of thyroid papillary carcinoma [ 47 ]. Studies have shown that the methylation of ADRA1B plays a key role in the occurrence and development of GC [ 48 , 49 ]. Our study showed that the expression of ADRA1B in GC tissues was lower than that in adjacent tissues, which may be related to methylation.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the cancers with better characterised tumorogenesis genetic pathways and one of the common alterations implicated in tumorogenesis is DNA methylation (20). Promoter methylation silences tumor suppressor genes in great number of neoplasias (21,22). p16 gene acts as a negative controller of cell cycle playing an important role as tumor suppressor (23).…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant methylation of gene promoters is a major mechanism for silencing tumor suppressors or other cancer-associated genes in many kinds of human cancers [16][17][18]. Genes such as CDH1, p16, MGMT, and APC have been found to harbor hypermethylated promoters in over 30% of colorectal tumors [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%